STUDENTS’ LANGUAGE LEARNING STRATEGIES DIFFERENCE IN AN INDONESIAN EFL SINGLE-GENDER CLASSROOM - Asep Kurnia (Universitas Perjuangan Tasikmalaya, 2019)
AbstractThe issue of single-gender classroom is identified as the preference classroom system in education around the world. This classroom system is adopted due to female and male students’ performance in the learning process including English subject. In Indonesia, the issue of single-gender classroom is not publically implemented, co-educational classroom is preferred. However, some cities are promoted the single-gender classroom, specifically the cities which promote the religious education such as in Tasikmalaya, West Java, Indonesia. Due to the pre-observation in a boarding school implemented the single-gender classroom, there is an exact different between female and male achievement in English classes. There are some factors affect the students’ achievement. Learning strategies is one of the most important thing influent the achievement. Therefore, the main focus of the research is observing different students preference in learning strategies. Questionnaire and interview are formed as data collecting techniques. Consequently, there was an exact different between female and male students in using language learning strategies. Female students are common in performing metacognitive learning strategy. While, male students are prefer in implementing cognitive learning strategy. In the comparison, female students use the learning strategies more often than the male student, specifically in metacognitive and social learning strategies.Keywords: Learning strategies, single-gender classroom, Female and male differences, Indonesian EFL classroom, Students’ achievement factors.